Lineage‐specific plasmid acquisition and the evolution of specialized pathogens in Bacillus thuringiensis and the Bacillus cereus group. Issue 7 (2nd April 2018) - Méric, Guillaume; Mageiros, Leonardos; Pascoe, Ben; Woodcock, Dan J.; Mourkas, Evangelos; Lamble, Sarah; Bowden, Rory; Jolley, Keith A.; Raymond, Ben; Sheppard, Samuel K.
Abstract: Bacterial plasmids can vary from small selfish genetic elements to large autonomous replicons that constitute a significant proportion of total cellular DNA. By conferring novel function to the cell, plasmids may facilitate evolution but their mobility may be opposed by co‐evolutionary relationships with chromosomes or encouraged via the infectious sharing of genes encoding public goods. Here, we explore these hypotheses through large‐scale examination of the association between plasmids and chromosomal DNA in the phenotypically diverse Bacillus cereus group. This complex group is rich in plasmids, many of which encode essential virulence factors (Cry toxins) that are known public goods. We characterized population genomic structure, gene content and plasmid distribution to investigate the role of mobile elements in diversification. We analysed coding sequence within the core and accessory genome of 190 B. cereus group isolates, including 23 novel sequences and genes from 410 reference plasmid genomes. While cry genes were widely distributed, those with invertebrate toxicity were predominantly associated with one sequence cluster (clade 2) and phenotypically defined Bacillus thuringiensis . Cry toxin plasmids in clade 2 showed evidence of recent horizontal transfer and variable gene content, a pattern of plasmid segregation consistent with transfer during infectious cooperation. Nevertheless, comparison between clades suggests that co‐evolutionary interactions may drive association between plasmids and chromosomes and limit wider transfer of key virulence traits. Proliferation of successful plasmid and chromosome combinations is a feature of specialized pathogens with characteristic niches ( Bacillus anthracis, B. thuringiensis ) and has occurred multiple times in the B. cereus group.